Bugs an expedition through the undergrowth - Green, Jen (San Diego, CA Silver Dolphin Books, 2012)
"Explore the extraordinary world of bugs with five spectacular 3-D pop-up scenes. You'll go deep into each habitat and get a unique look at fascinating creatures from around the globe. Dramatic 3-D scenes bring each habitat to life. "--Cover back
Ages 7 and up
2
NEW
Keywords: Animals; Insects; Pop-up books; Toy and movable books